Reuse Markets: Embedded in Capitalism - Egbert, Henrik (Journal of Entrepreneurship, Business and Economics, 2024)
The paper addresses the growing popularity of markets for reuse and repair (RR) in a developed economy. The reasons behind the growth of these markets remain an open research question, which could be attributed to changing consumer preferences and/or as an effect of multiple exogenous shocks on societies. The paper contributes to the predominantly anthropological research on the topic by employing a market-oriented entrepreneurial perspective. The methodology involves participant observation by actively engaging as a trader in micro activities to exploit arbitrage opportunities. The findings suggest that the traditional economic model of rational actors is well-suited to analyze individual actions in these markets. It is observed that these markets do not necessarily require integration into complex social constructs. Effective trust-building arrangements with low transaction costs facilitate market transactions between strangers. The research implies the importance of markets at the micro level, especially in times when political actors at the macro level favor market interventions. Research Paper Keywords: second-hand markets; reuse and repair activities; economic approach to anthropology; informal market; consumption; ebay Kleinanzeigen Reference to this paper should be made as follows: Egbert, H. (2024). Reuse Markets: Embedded in Capitalism. Journal of Entrepreneurship, Business and Economics , 12 (1), 1–35.